Les chansons de Bilitis - Louÿs, Pierre 1870-1925; Mondor, Henri 1885-1962; Galanis, Démétrius Emmanuel 1882-1966 (Paris Gallimard, 1990)
'The Songs of Bilitis' is a collection of erotic, essentially lesbian, poetry by Pierre Louÿs published in Paris in 1894. Since Louÿs claimed that he had translated the original poetry from Ancient Greek, this work is considered a pseudotranslation. The poems were actually clever fabulations, authored by Louÿs himself, and are still considered important literature.The poems are in the manner of Sappho; the collection's introduction claims they were found on the walls of a tomb in Cyprus, written by a woman of Ancient Greece called Bilitis (Greek: Βιλιτις), a courtesan and contemporary of Sappho to whose life Louÿs dedicated a small section of the book. On publication, the volume deceived even expert scholars.Louÿs claimed the 143 prose poems, excluding 3 epitaphs, were entirely the work of this ancient poet—a place where she poured both her most intimate thoughts and most public actions, from childhood innocence in Pamphylia to the loneliness and chagrin of her later years.
Pierre Louÿs (1870-1925) was a French poet and writer, most renowned for lesbian and classical themes in some of his writings. He is known as a writer who sought to "express pagan sensuality with stylistic perfection". He was made first a Chevalier and then an Officer of the Légion d'honneur for his contributions to French literature.
Originally published in 1898
Keywords: 20th Century (1901-2000); Poetry; Literature; Female; Paris (France)